Recent trends and methodologies in gold nanoparticle synthesis - A prospective review on drug delivery aspect - Manimegalai Sengani; Alexandru Mihai Grumezescu; V. Devi Rajeswari (Elsevier, 2017)
The prominent challenges in manufacturing carrier systems for chemical, biological and medical applications are to produce stable, nontoxic and uniform dimension particles by using various macromolecules. In this respect, the emerging field of nanotechnology enables various approaches towards optimizing synthesis protocols and methodologies. Depending on the application of the particles, various methodologies for nanoparticle synthesis have been adopted. Especially, gold nanoparticles (AuNPs) have tremendous potential for bionanotechnology-based applications, thus resulting in new possibilities and insights within the medical research field. These nanoparticles can be used for selective transportation mechanism through receptor ligand binding. During various synthesis processes of AuNps, several difficulties have been encountered. Therefore, the scientific research community turned its attention towards tuning and perfecting the obtaining approaches involved in AuNPs synthesis. This review aims to facilitate the understanding of different strategies used for AuNPs synthesis, as well as highlighting the challenges and future perspectives of AuNPs in bionanotechnology.